2019
DOI: 10.4025/actascibiolsci.v41i1.42174
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium toxicity on seed germination and initial growth of chia

Abstract: In recent years, there has been a growing concern related to soil and water contamination due to the constant dispersal of toxic metals. In addition to their ecotoxicological potential, these elements exhibit a cumulative character that favors their permanence in soil and passage to living organisms, which can lead to an ecological imbalance. Among toxic metals, cadmium (Cd) is an obstacle to agriculture because it can adversely affect food quality and human health, as well as diminish plant growth and product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…For instance, Vashisth and Nagarajan (2010) reported that magnetoprimed wheat and sunflower seeds had significantly higher amylase activity than their controls. Previous studies have reported higher α-amylase and protease activity in magnetoprimed soybean and maize seedlings under various stress conditions such as salt, mercury toxicity and UV-B (Kataria et al 2017, 2019, 2020, 2023, Raipuria et al 2021, Prajapati et al 2023). The higher protease activity in magnetoprimed seeds could contribute to the breakdown of stored proteins into amino acids (Rajendra et al 2005) that can be utilized for energy and growth during seedling development.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…For instance, Vashisth and Nagarajan (2010) reported that magnetoprimed wheat and sunflower seeds had significantly higher amylase activity than their controls. Previous studies have reported higher α-amylase and protease activity in magnetoprimed soybean and maize seedlings under various stress conditions such as salt, mercury toxicity and UV-B (Kataria et al 2017, 2019, 2020, 2023, Raipuria et al 2021, Prajapati et al 2023). The higher protease activity in magnetoprimed seeds could contribute to the breakdown of stored proteins into amino acids (Rajendra et al 2005) that can be utilized for energy and growth during seedling development.…”
Section: Discussionmentioning
confidence: 95%
“…It is often found in industrial and agricultural waste and can contaminate soil, water, and food (Yin et al 2021). The germinating seed serves as the first point of interaction between the developing plant and its surrounding environment, making it particularly susceptible to the toxic effects of Cd (Stefanello 2019, Mahawar et al 2021. Cd significantly inhibited the seed germination of various plant species such as swiss chard, lettuce, wheat, basil, chia, beans and spinach (Ahmad et al 2012, Bautista et al 2013, El Rasafi et al 2016, Gharebaghi et al 2017, Stefanello 2019.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation